Analisis Kapasitas Fasilitas Boarding di Bandar Udara Sultan Hasanuddin Makassar - Jeni Sartika (Research and Development Agency of The Ministry of Transportation, 2011)
Sultan Hasanuddin International Airport Makassar with its role as the entrance to eastern part of Indonesia, is the busiest airport currently. However, it may mean nothing if it is not facilitated with boarding lounge both for domestic and international departure. Boarding lounge is a place provided for passengers to wait before departure after they check ini. Due to the busy airport, potentials of flight delay experienced by the passengers while waiting in the boarding lounge should be anticipated. It may happen because of the congested passengers during peak hours. Nevertheles, after Conducting this research, results show that the utilization of the provided boarding lounge reaches 67% while the passenger perception towards the facilities is categorized very good. On the other hand, the calculation of the provided boarding lounge capacity show